PENGARUH PILAR JEMBATAN PANGO TERHADAP POLA ALIRAN SUNGAI KRUENG ACEH - Putra, Teuku Devansyah; Fatimah, Eldina; Azmeri, Azmeri (JURNAL TEKNIK SIPIL, 2018)
Abstract: Pango Fly Over is located in the coordinate of 50 32' 07.32" LU (North Latitude) and 950 20' 52.90 BT (East Longitude) on Pango Village, Ulee Kareng Sub District, Banda Aceh. This bridge was built across Krueng Aceh River and the pillars were built in the river so that it narrows the river cross section and affecting the increasing of flow velocity. From the research location observation, it is found that the bridge pillars cause the more narrowing of the river cross section and there is the damage of the riverbank around the river bend located in the downstream of the pillars. If there is no further follow up, it will erode the national road. This research aims to find out flow pattern without and with the pillars, and to know the flow pattern behavior in the river bend. This research uses Surface Water Modeling System (SMS Version 11.2) Program. The length of the river reviewed is 500 meters. The flow discharge used in this research is the flood discharge which the period is Q 100 and the value is 627.74 m/second (passing the Pango Fly Over). From the result of the flow patter simulations, it is obtained that the maximum flow velocity without the pillars found in the middle location of V3 reviewed point on the distance 45 m from the riverbank is 0.45 m/sec and maximum flow velocity with the pillars found in the middle location of V3 reviewed point on the distance 33 m from the riverbank is 0.35/sec. In the outer bend of the flow pattern simulation result without pillars, it is obtained that the maximum velocity found in V6 reviewd location on the distance 50 m is 0.83 m/sec in the left side of the flow.Meanwhile in the downstream of the bend, the maximum velocity wit the bridge pillars found in V6 reviewd location on the distance 50 m is 0.95 m/det in the left side of the flow. In the bridge pillars downstream location, there is the river bend required the riverbank reinforcement and the riverbed reinforcement in order to avoid the erosion in the riverbank, because it will endanger the public facilities.Abstrak: Jembatan fly over Pango berada pada koordinat 50 32' 07.32" LU dan 950 20' 52.90 BT terletak di desa Pango Kecamatan Ulee Kareng kota Banda Aceh. Jembatan ini di bangun melintang Sungai Krueng Aceh dan pilar jembatan dibangun pada sungai sehingga terjadi penyempitan penampang sungai yang menyebabkan kecepatan aliran bertambah, Dari tinjauan lokasi penelitian pilar jembatan semakin mengalami penyempitan penampang sungai dan terjadi kerusakan tebing di sekitar belokan sungai yang berada di hilir jembatan. Bila tidak segera di tindak lanjuti akan berdampak tergerusnya jalan nasional. Penelitian ini bertujuan untuk mengetahui pola aliran tanpa adanya pilar dengan adanya pilar serta untuk mengetahui perilaku pola aliran yang terjadi pada belokan sungai. Penelitian ini menggunakan program Surfacewater Modeling System (SMS. Versi 11.2). Panjang sungai yang di tinjau 500 meter. Debit aliran yang digunakan pada penelitian ini mengunakan debit banjir periode ulang Q-100 tahunan yaitu 627,74 m/detik (yang melewati jembatan fly over Pango). Dari hasil simulasi pola aliran didapatkan besaran kecepatan aliran tanpa pilar pada lokasi tengah aliran pada titik tinjauan V3 dengan jarak 45 m dari tanggul sungai kecepatan maksimumnya 0,45 m/det dan besaran kecepatan aliran dengan adanya pilar jembatan pada lokasi tengah pilar pada titik tinjauan V3 dengan jarak 33 m dari tanggul sungai kecepatan maksimumnya 0,35 m/det. Pada belokan luar dari hasil simulasi kecepatan aliran tanpa pilar besaran kecepatan maksimum pada titik tinjau V6 dengan jarak 50 m yaitu 0,83 m/det pada kiri aliran. Sedangkan di hilir belokan pada titik tinjau V6 dengan jarak 50 m dengan adanya pilar jembatan besaran kecepatan maksimum yaitu 0,95 m/det kiri aliran. Pada hilir pilar jembatan terdapat belokan sungai yang memerlukan perkuatan tebing dan perkuatan dasar agar tidak terjadi erosi di tebing sungai, sebab hal ini dapat membahayakan terhadap fasilitas umum.